Acute respiratory distress syndrome after aspiration of lamp oil in a fire-eater: a case report. (December 2016) - Behnke, Nico; Breitkreuz, Jekaterina; Buck, Cordula; Hinterthaner, Marc; Emmert, Alexander
Abstract Background Fire-eater's pneumonia is an exogenous chemical pneumonitis after accidental aspiration of hydrocarbon fluids during the act of fire-eating. There have been few case reports in the literature regarding complications after fire-eating but so far none, to the best of our knowledge, have described such drastic and life-threatening pulmonary complications as in this case while only having swallowed a small amount of fluid. Case presentation We present a case of fire-eater's pneumonia in a 28-year-old white man with severe pulmonary complications. He presented with pneumonitis and partial respiratory insufficiency. He was diagnosed with acute respiratory distress syndrome and was treated with antibiosis, oxygen therapy, and required non-invasive ventilation. He had a good recovery. Conclusions Accidental aspiration of even small amounts of lamp oil can lead to serious life-threatening pulmonary complications. Although fire-eaters are a comparatively small occupational group, the severity of possible complications illustrates that awareness of these consequences should be raised in teenagers and young adults who might be tempted into trying it. This case in a Western country shows that the dangers of fire-eating are not to be underestimated and are not limited to Eastern European countries where the majority of cases have been reported.